Mozart i śpiewacy: ograniczenie czy inspiracja? - Brandenburg, Daniel (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Stefan Kunze called the time before Mozart settled in Vienna the years of migration and study. Daniel Brandenburg in his article shows that in reference to the operas composed by young Mozart for Milan (Mitridate re di Ponto, 1770, Lucio Silla, 1772) and Munich (Idomeneo re di Creta, 1781), the process of education meant also mastering the Italian singing conventions. Composing for singers appears to be an inspirational task, although it was limited in various ways. That double effect is recorded in Mozart’s scores.